Evaluation of the physiological and psychological impact of easter lent fasting in obese individuals: emphasis on anthropometry, lipid profiles, liver functions, and mood - Poikunnel Chacko, Jincemol; Shetty, Prashanth; Shetty, Geetha B. (International Journal Of Community Medicine And Public Health, 2025)
Background: Obesity is a significant global public health concern due to its persistent metabolic disorder status. While dietary interventions during religious fasting have shown benefits in weight and biochemical improvements, limited evidence exists on the effects of Easter Lent fasting. The current study aimed to evaluate the physiological and psychological impact of easter lent fasting in obese individuals. Methods: The study was conducted on 60 subjects, including overweight and grade 1 obese individuals, in two different periods, specifically a normal routine dietary regimen and a period of the Easter lent in Kerala. The baseline assessment was done on anthropometry, lipid profile, liver enzymes, and profile mood states at the beginning and after six weeks, where participants followed a non-vegetarian diet as a normal routine diet. After a week's hiatus the assessment was repeated, and they abstained from all animal-based foods and followed a vegetarian diet, time-restricted eating on Fridays, accompanied by prayer and meditation. Results: Easter Lent fasting resulted in significant reductions in body weight, BMI, waist-hip ratio, total cholesterol, triglycerides, LDL, VLDL, lipid ratios (TC/HDL, LDL/HDL), and liver enzymes (SGOT, SGPT). A significant reduction in negative thoughts and total mood disturbance was also observed, indicating a positive impact on both the psychological and physiological well-being of obese individuals. Conclusion: The practice of Easter lent fasting has demonstrated notable decreases in body mass, lipid profiles, and hepatic function, accompanied by a pronounced reduction in total mood disturbance.